Exploring Bandung Public Bus Commuter Satisfaction and Loyalty - Faridian Wirayat, Mohamed Yusuf; Belgiawan, Prawira Fajarindra (The Asian Journal of Technology Management (AJTM), 2023)
Bandung, the capital of West Java, is 2021 Indonesia's most crowded city. Congestion happens even then since the number of cars in Bandung has grown by an average of 11% annually. To overcome the congestion, the Ministry of Transportation Republic Indonesia programme created the "Teman Bus" programme in December 2021. Therefore, this study explores the impact of factors influencing passenger loyalty towards public bus services. A cross-sectional survey of bus users in Bandung was conducted in June 2022, with 211 respondents. The data were analysed using structural equation modelling. Using PLS-SEM, the relationship between constructs and loyalty was examined, and importance-performance map analysis was used to determine which drivers should prioritise increasing levels of a target construct of interest. The results indicate that perceived safety and security, perceived service quality, and image significantly influence loyalty. It also implies that those three variables, as revealed by the study's findings of the importance and performance matrix, need to be improved to increase customer loyalty when it comes to bus services.